Analisis Konsep Kawin Hamil pada Film Dua Garis Biru Perspektif Hukum Positif Indonesia dan Hukum Islam - Emiliya Ehsaniyah (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2020)
Nowadays, there are many cases of marriage for pregnant women, this is one of the effects of too free association between men and women. The phenomenon of pregnant marriage as a result of promiscuity among adolescents is reflected in the film Two Blue Lines. In Islamic law, people who engage in husband and wife relations outside of a legal marriage are punished as adultery. If the adultery results in pregnancy and marriage, the priests of the Madzhab have different opinions regarding the validity of the marriage and also the status of the child in the womb. Whereas in positive law (Marriage Law and KHI), the marriage of a pregnant woman is legal and the status of the child who is born later is categorized as a legal child. The purpose of this study was to determine and analyze the concept of pregnant marriage contained in the scenes of the film Dua Lines Biru to be analyzed using Law No.1 of 1974 concerning Marriage, Islamic Law, and Compilation of Islamic Law.